Dialogues of Cultures: French Musical Orientalism in Russia, “Artistic Truth,” and Russian Musical Identity - Issiyeva, Adalyat (Revue musicale OICRM, 2016)
The influence of the Saisons Russes, with its utterly Orientalist appeal in defining French modernism and Western avant-garde culture in general, is widely known and discussed by many researchers from multiple perspectives (Schaeffner 1953, Garafola 1989, Davis 2010, Bellow 2013). Less emphasised to date is the fact that Russian Orientalism emerged from European stimuli and, in many respects, its very existence is indebted to French Orientalism. As the famous Russian Orientalist Vasily Bartol’d complained, “The Orient’s neighbour, Russia, despite its geographical proximity, often preferred reading shoddy Western books on the Orient to a direct study of the Orient” (Bartol’d 1925, p. 295). 1 This occurred as a result of the nineteenth-century travels of many Russian literary men, painters, and linguists to Europe (notably to France and Germany) to study with famous Orientalists. This paper contextualizes French Orientalism within nineteenth-century Russian culture and considers how French musical Orientalism was negotiated in Russian writings from the period. Despite the critical views of Russian musicians toward French music with oriental subjects, the music nevertheless resonated with Russian compositional practices and some of its devices were used occasionally to depict not only the Orient, but Russia itself.